Upaya Meningkatkan Minat dan Hasil Belajar Siswa Melalui Model Discovery Learning Pada Materi Hereditas di Kelas XII IPA 4 SMAN 22 Bandung - RATU NAHDIAH (Universitas Pasundan, 2021)
This Classroom Action Research aims to determine the increase in student interest and learning outcomes in heredity material through the application of discovery learning models. The research subjects were students of class XII IPA 4 SMAN 22 Bandung totaling 36 people. The research design used adopted a classroom action research procedure model adapted from Hopkins. Each cycle consists of four main activities, namely planning, implementation, observation, and reflection. The research data is in the form of information about the results and the learning process of the discovery learning model with the data collection techniques used are observation, tests, and questionnaires. The results showed an increase in the average score of interest from 61.27% in the first cycle to 78.61% in the second cycle. Student learning outcomes also showed an increase as seen from the increase in the value of classical absorption from the first cycle of 65% to 87.50% in the second cycle. The student's response to the use of the discovery learning model was very positive, as seen from the results of the questionnaire distributed to students. In general, students like the use of discovery learning models, this is because the discovery learning model makes them more active in learning and better able to understand the existing material critically and creatively, as well as being able to find solutions to the problems at hand, so it can be concluded that the model discovery learning on heredity material can increase the interest and learning outcomes of class XII IPA 4 SMAN 22 Bandung